12th EASN International Conference on Innovation in Aviation & Space for Opening New Horizons (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue contains selected papers from works presented at the 12th EASN (European Aeronautics Science Network) International Conference on Innovation in Aviation & Space for Opening New Horizons, which was held from the 18th until the 21st of October 2022, in Barcelona, with physical participation. About 470 participants contributed to a high-level scientific gathering providing some of the latest research results on the topic, as well as some of the latest relevant technological advancements. Twenty interesting papers, which cover a wide range of topics including characterization, analysis and design, as well as numerical simulation, are contained in this Special Issue.